Quantum mechanical study of the influence of noble metals on the process of reduction of uranium oxides - A.S. Vorob'ev; A.Y. Galashev; Yu P. Zaikov (Nuclear Engineering and Technology)
A DFT study of electrochemical reductions of uranium oxides in the presence of noble metals was performed. The study focused on the effects produced by the presence of Ag, Au, Pt and Pd on the rate of UOx reduction and on the composition of the resulting product. The noble metals that make up uranium oxides, to varying degrees, bring the reduced material to the stage of direct reduction, i.e. obtaining metallic uranium without the chemical reaction of binding oxygen with a light metal. Silver and gold initiate the process of direct reduction of uranium oxides more efficiently than platinum and palladium. The electronic conductivity of the reduced oxide in the presence of Ag and Au appears when there is a greater amount of oxygen in the system than is the case in the presence of Pt or Pd in the system.